2011
DOI: 10.5194/os-7-203-2011
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tides on dense water formation in Arctic shelf seas

Abstract: Abstract. Ocean tides are not explicitly included in many ocean general circulation models, which will therefore omit any interactions between tides and the cryosphere. We present model simulations of the wind and buoyancy driven circulation and tides of the Barents and Kara Seas, using a 25 km × 25 km 3-D ocean circulation model coupled to a dynamic and thermodynamic sea ice model. The modeled tidal amplitudes are compared with tide gauge data and sea ice extent is compared with satellite data. Including tide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…The tidal mixing over topography controls the northward extension of temperate AW and thus sea ice cover variability (Holloway and Proshutinsky, 2007), and enhances dense water formation (Postlethwaite et al, 2011). Recent numerical model results show that there is significant internal tidal wave generation in the Arctic Ocean, with baroclinic tidal energy dissipation structures similar to but 2-3 orders of magnitude less than that observed on mid-Atlantic and Hawaiian ridges (Kagan et al, 2011).…”
Section: Diapycnal Mixing In the Arctic Oceanmentioning
confidence: 99%
“…The tidal mixing over topography controls the northward extension of temperate AW and thus sea ice cover variability (Holloway and Proshutinsky, 2007), and enhances dense water formation (Postlethwaite et al, 2011). Recent numerical model results show that there is significant internal tidal wave generation in the Arctic Ocean, with baroclinic tidal energy dissipation structures similar to but 2-3 orders of magnitude less than that observed on mid-Atlantic and Hawaiian ridges (Kagan et al, 2011).…”
Section: Diapycnal Mixing In the Arctic Oceanmentioning
confidence: 99%
“…To our knowledge, with the exception of a regional study by Postlethwaite et al . [], there have been no previous modeling studies that consider the effects of tides on the AO by comparing numerical simulations with and without explicitly resolved tides. Although we note that Koentopp et al .…”
Section: Introductionmentioning
confidence: 99%
“…An overview of the ocean currents and circulation in the Barents Sea from model studies can be found (e.g., Maslowski et al, 2004;Aksenov et al, 2010;Postlethwaite et al, 2011). All the authors show the AW slope-current in the Nansen Basin, and Maslowski et al (2004) and Aksenov et al (2010) also show its branching off bringing AW into the NBSO.…”
Section: Introductionmentioning
confidence: 99%